Correlation and path coefficient analysis of seed yield and yield related characters in sesame (Sesamum indicum L.): CORRELATION AND PATH COEFFICIENT ANALYSIS OF YIELD AND YIELD CHARACTERS IN SESAME - S R KUMHAR; BABITA KUMARI; SUSHILA SIROHI (Journal of Oilseeds Research, 2020)
Correlation and path analysis were carried out to determine the effects of various traits as components of seed yield in 40 sesame genotypes. The genotypes were evaluated in RBD with three replications during kharif 2018 at the Research Farm of Agricultural Research Station, Agriculture University, Jodhpur, Rajasthan. Analysis of variance exhibited significant difference for all the characters suggesting the presence of inherent genetic variations among the genotypes studied. Correlation among the traits revealed that seed yield/plant was positively associated with number of capsules/plant, capsule bearing length, harvest index and number of primary branches at both genotypic and phenotypic levels, while, non-significant correlation with days to 50% flowering, days to maturity, plant height (cm), number of seeds per capsule and 1000-seed weight. The path coefficient analysis of different characters contributing towards seed yield/plant showed positive direct effect by number of capsules/plant. Capsule bearing length, harvest index, number of primary branches/plant, 1000-seed weight, plant height and days to 50% flowering showed considerable positive direct effect on seed yield. Indirect positive effect showed by days to 50% flowering via number of primary branches at genotypic level. These results indicated that number of primary branches/plant, number of capsules/plant, capsule bearing length and harvest index are the principal yield components, and selection for these traits may be useful in improving seed yield in sesame.